2020
DOI: 10.1186/s12943-020-01249-8
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of METTL14 mediates the elevation of PERP mRNA N6 adenosine methylation promoting the growth and metastasis of pancreatic cancer

Abstract: Background: Pancreatic cancer is one of the most lethal human cancers. N 6-methyladenosine (m 6 A), a common eukaryotic mRNA modification, plays critical roles in both physiological and pathological processes. However, its role in pancreatic cancer remains elusive. Methods: LC/MS was used to profile m 6 A levels in pancreatic cancer and normal tissues. Bioinformatics analysis, real-time PCR, immunohistochemistry, and western blotting were used to identify the role of m 6 A regulators in pancreatic cancer. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
172
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(178 citation statements)
references
References 50 publications
3
172
2
1
Order By: Relevance
“…The role of METTL14 and IGF2BP3 in human cancers was studied before. The promotion function by METTL14 in pancreatic cancer was uncovered ( 75 ) and IGF2BP3 was found to be a potential prognosis marker and therapeutic target of colon cancer ( 76 ). Yet the miRNA-mediated mechanisms of METTL14 and IGF2BP3 , if any, remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The role of METTL14 and IGF2BP3 in human cancers was studied before. The promotion function by METTL14 in pancreatic cancer was uncovered ( 75 ) and IGF2BP3 was found to be a potential prognosis marker and therapeutic target of colon cancer ( 76 ). Yet the miRNA-mediated mechanisms of METTL14 and IGF2BP3 , if any, remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The role of CRABP2 and NUSAP1 in pancreatic cancer is currently unclear, but CRABP2 and NUSAP1 favors proliferation and invasion of several types of tumor, such as prostate, lung, gastric and colorectal cancer ( Gordon et al, 2017 ; Han G. et al, 2018 ; Wu et al, 2019 ; Ge et al, 2020 ; Xu et al, 2020 ). Interestingly, a recent study showed that knocking down the expression of PERP in pancreatic cancer cells promotes proliferation and invasion of the cells, suggesting a tumor-suppressive function of PERP in pancreatic cancer ( Wang et al, 2020 ). Indeed, PERP has a well-known pro-apoptotic function by dependently or independently of p53 signal pathways, and loss of the gene is linked to tumorigenesis ( Attardi et al, 2000 ; Beaudry et al, 2010 ; McDonnell et al, 2019 ; Awais et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…After boiling at 100 • C for 5 min, the equal amounts of protein extract were electrophoresed in a 10% sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PAGE) at 80 V for 20 min and then 120 V for 1 h. Subsequently, the protein extract was transferred to PVDF membranes (Biosharp, Shanghai, China) at 220 mA for 60 min. After repeated washing using tris-buffered saline containing Tween 20 (TBST), the PVDF membranes were blocked with 5% bull serum albumin (BSA) blocking buffer for 2 h at 37 • C, and then incubated with primary antibody collagen I, 1:1,000; collagen III, 1:1,000; α-smooth muscle actin (α-SMA), 1:1,000; Epac1, 1:1,500; p-Akt, 1:1000; t-Akt, 1:1,000; p-PI3K, 1:1000; t-PI3K, 1:1,000; GAPDH, 1:2,500 overnight at 4 • C. Afterward, the PVDF membranes were incubated with a secondary antibody (anti-rabbit IgG, HRPlinked antibody, 1:5,000; anti-mouse IgG, HRP-linked antibody, 1:5,000) for 1 h at 37 • C (Wang et al, 2020b). Finally, signals were visualized using the enhanced chemiluminescence (ECL) detection kit (Yeasen, Shanghai, China), and the relative protein abundance was measured by ImageJ image analysis software (version 1.44p, National Institutes of Health, United States).…”
Section: Western Blot Analysismentioning
confidence: 99%